The Linguistic Phenomenon Found in the Instagram Caption Account of the @bahasa_bali - Muliawan, Made Sani Damayanthi (e-Journal of Linguistics, 2021)
This research is entitled "The Linguistic Phenomenon Found in the Instagram Caption Account of the @bahasa_Bali" which aims to find the code mixing and code switching for the linguistic phenomenon contained in the Instagram caption of the @bahasa_bali account. The data collected was analyzed descriptively using qualitative methods in the Instagram caption of the @bahasa_bali account. The data in the form of code switching and code mixing in the speech found on the caption are analyzed for the function of the speech act using Searle's version of speech act theory which divides speech acts into three namely locutionary, illocutionary, and perlocutionary. From the results of this study, it can be concluded that the form of code switching and code mixing in the speech contained in the Instagram @bahasa_bali caption is in the form of words and phrases. The speech acts of code switching and code mixing are in the form of locutionary and illocutionary speech acts which have assertive, directive, and expressive functions. The factors in the use of code switching in speech are because Balinese language which is the main language has not been able to provide equivalent words that are in accordance with the intentions of the speaker and speech partner. The factors that influence the use of code mixing in everyday speech are both speakers and speech partners who both master Balinese, Bahasa and English so that there is contact between the three languages both national languages, regional, and foreign in a communication.